Proximate Analysis and Antioxidant Properties of Young Plants of Sinapis alba L. Depend on the Time of Harvest and Variety - Urszula Sadowska; Klaudia Jewiarz; Magdalena Kopak; Kinga Dziadek; Renata Francik; Aneta Kopeć (Applied Sciences, 2023)
White mustard plant (Sinapis alba L.) is an easy-to-grow species with low soil requirements and is often sown as a catch crop in Northern Europe to reduce nitrate leaching, especially during the winter. There are studies showing the high nutritional value of mustard seeds, which have a wide application, mainly in food production. Still little is known about the young shoots or plants of different cultivars of white mustard, although in Asian countries, eating them raw is quite common. The aim of the research was to determine the proximate composition, antioxidant activity and polyphenolic compound content in young green plants of the Polish cultivars of white mustard: Borowska (traditional, with a high content of erucic acid and glucosinolates), Bamberka (non-erucic with glucosinolates) and Warta (non-erucic with low glucosinolates content; double-improved). Young plants were harvested in three terms. The first harvest took place at the plover stadium and the next ones at 7-day intervals (31, 38 and 45 day after sowing). In freeze-dried plant material, proximate composition and antioxidant activity with the ABTS and FRAP methods, as well as phenolic compound content, were measured. The highest concentration of protein was measured in cultivars Warta and Borowska after 31 and 38 days of sowing. Harvest time and cultivar affected antioxidant activity and total polyphenol content in young mustard plants. Thirty-eight days after sowing, the examined cultivars of the young plants of mustard had the highest antioxidant activity and total polyphenolic compound content. Green young mustard plants have strong antioxidant properties at the basic level, they are classified as functional foods and are similar to other edible leafy plants such as celery, spinach and Brussels sprouts.